1988
DOI: 10.3109/00016488809119525
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Head and Brainstem Size to Main Parameters of ABR in the Developmental Age and in Adults

Abstract: In a previous investigation the relationship between head size and main parameters of ABR, i.e. waves absolute latencies and interwave delays, was studied in 55 subjects (1). Significant and positive correlation coefficients were found between I-V I.P.I. and the sum of head circumference, nasion-inion, and intertragal distances in the age range 7 to 11 years only and not in adult age. The purpose of the present study was to verify whether in 11 adults a correlation could be demonstrated between ABR parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…This striking correspondence of our electrophysiological data and the anatomical data of Sato et al strongly suggests that this difference in anatomical length has not changed the tonotopic mapping but has been compensated by an alteration in the stiffness gradient. Finally, an intergender difference in the cochlear response time may be the additional variable to account for the wave V latency difference between genders that could not be wholly explained by physical variables such as head size and dimensions of neural structures (Patterson et al, 1981;Antonelli, 1988;Elton, 1988;Durrant et al, 1990;Sabo et al, 1992).…”
Section: It May Be Difficult To Understand How Wave I (And Therefore mentioning
confidence: 99%
“…This striking correspondence of our electrophysiological data and the anatomical data of Sato et al strongly suggests that this difference in anatomical length has not changed the tonotopic mapping but has been compensated by an alteration in the stiffness gradient. Finally, an intergender difference in the cochlear response time may be the additional variable to account for the wave V latency difference between genders that could not be wholly explained by physical variables such as head size and dimensions of neural structures (Patterson et al, 1981;Antonelli, 1988;Elton, 1988;Durrant et al, 1990;Sabo et al, 1992).…”
Section: It May Be Difficult To Understand How Wave I (And Therefore mentioning
confidence: 99%
“…A previous study has suggested that brain size has an influence on the latency of BAEP waves [14], and the relevant brain feature is thought to be the length of the auditory neural pathway. This finding is supported by documentation of the correlation between BAEP latencies and brain stem length as measured using magnetic resonance imaging views of the human brain stem [1].…”
mentioning
confidence: 52%
“…The results showed that head circumference in the preterm SGA infants (32.9 ± 2.2) was significantly smaller than that in the AGA term infants (35.0 ± 1.4) (p < 0.01, Table 1). It is known that the size of the head affects the measurement of BAER variables, particularly during early development (17)(18)(19). To find any relationship between BAER findings and head size in the preterm SGA infants and to examine whether any BAER abnormalities in the preterm SGA infants are related to their smaller head size, the correlation between the measurements of BAER variables and head circumference was analysed.…”
Section: Correlation Between Baer Results and Head Circumferencementioning
confidence: 99%
“…the distance between the recording electrodes and the location of the generators of the evoked potentials. In the adult the I-V and III-V intervals correlate positively with head circumference; the smaller the head the shorter the I-V and III-V intervals, because of the shorter neural pathway (17)(18)(19). In the infant the relationship between BAER intervals and head circumference is complex and changes as a function of age, which is related to myelination and synaptic development of the brainstem during maturation (17,19).…”
Section: Baer Abnormalities Following Iugr Are Associated With Small mentioning
confidence: 99%